2001
DOI: 10.1111/j.1348-0421.2001.tb02607.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in 16S‐23S rDNA Internal Transcribed Spacer Regions and the Possible Use of This Genetic Variation for Molecular Diagnosis of Bacteroides Species

Abstract: Abstract:The structural variation in 16S-23S rDNA internal transcribed spacer regions (ITS) among Bacteroides species was assessed by peR amplification and sequencing analysis, and its possible use for molecular diagnosis of these species was evaluated. Ninety strains of the genus Bacteroides, including the species B. distasonis, B. eggerthii, B.fragilis, B. ovatus, B. thetaiotaomicron, B. uniformis and B. vulgatus, produced one to three ITS amplification products with sizes ranging from 615 to 810 bp, Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Real‐time PCR was performed to confirm the B. uniformis bloom detected at week 11. Primers 16F2 and 23R4 (Table 1) were used to amplify the rrn ITS from week 11 DNAs and amplicons were cloned into pGEM‐T (Kuwahara et al , 2001). Bacteroides uniformis ITS‐containing plasmid pBu25 was identified by sequence analysis and subsequently used as the positive control for these experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Real‐time PCR was performed to confirm the B. uniformis bloom detected at week 11. Primers 16F2 and 23R4 (Table 1) were used to amplify the rrn ITS from week 11 DNAs and amplicons were cloned into pGEM‐T (Kuwahara et al , 2001). Bacteroides uniformis ITS‐containing plasmid pBu25 was identified by sequence analysis and subsequently used as the positive control for these experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The application of 16S rDNA PCR-RFLP to species identification offers a rapid and accurate approach for identification of Bacteroides to the species level. A similar strategy was used by Kuwahara et al (2001) to examine the 16S and 23S rRNA internal transcribed spacer region among Bacteroides spp. Amplification products of the spacer region digested with MspI produced distinctive species-specific RFLP patterns, and it was possible to differentiate 90 strains to the species level, including B. fragilis, B.…”
Section: Molecular Approachesmentioning
confidence: 99%
“…A DNA^DNA hybridization study by Johnson and Ault led to the distinction of two DNA homology groups, I and II [3]. We also showed the heterogeneity of this anaerobe by PCR-ribotyping using 16S^23S rDNA internal-transcribed spacer sequences [4]. It has also been reported that the pathogenic potential and antimicrobial susceptibility of B. fragilis vary among strains [5,6].…”
Section: Introductionmentioning
confidence: 84%